The Consequences of PCBs and BPA Resulting from Terrorist Operations in Three Regions of Baghdad on Thyroid Function - Jawad, Alaa H; Kadhim, Sara J; Al-Qaisi, Zyad H Jawad (Al-Nahrain Journal of Science, 2018)
Persistent organic pollutants polychlorinated biphenyls (PCBs) and bisphenol-A (BPA) are widely known of being toxicants. Exposure to a variety of dangerous toxic effects has been attached in all humans .in this paper the effect of terrorist operation on thyroid gland functions in a sample of Iraqi individual (AL-karradah and Abo-Gharib) comparison with Al-jadria rejoin as (control). The correlation between sera thyroid hormones thyroxine T4, triiodothyronine T3, Thyrotropin TSH and the levels of polychlorinated biphenyls (PCBs) and bisphenol-A (BPA) have been measured. 75 volunteers from three Iraqi areas were included in this study‎. Their ages ranged between (15-65) years. Our examination proposes an inverse relationship between BPA presentation and thyroid hormones. In this manner, increased persistent organic pollutants exposure might be a factor in the causes of hypothyroidism ‎and thyroid gland function. The result of this study showed that the effect of persistent organic pollutants polychlorinated biphenyls (PCBs) and bisphenol-A (BPA) on thyroid hormones, and the effect of military and terrorist operations on the thyroid gland. In the end we concluded that persistent organic pollutants resulting from the explosions and terrorist operations in the area of (Al-karadah, Abo-Gharib) high compared with the control (Al-jadria) as the lowest percentage of pollution, this leads to many diseases on the health of the human body and also the effect of persistent organic pollutants on the thyroid gland and its negative effect on thyroid hormones and cause thyroid disease.